Muscling toward therapy with ERBB3 and NGFR. Issue 1 (January 2018) - Ho, Andrew; Blau, Helen
To overcome the finite supply of muscle stem cells available for cell therapy, a study now describes a strategy for obtaining an unlimited source of myogenic progenitors derived from human pluripotent cells. Two neuronal cell surface receptors facilitate the selection of a population with enhanced regenerative potential.